Selection of Rhizobium leguminosarum strains for the inoculation of peas on the Rio de Janeiro hill farms - Conceição, Mauro da; Pereira, Newton N.C.; de-Polli, Helvécio; Franco, Avílio A.; Dobereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
In two greenhouse and one field experiments the inoculation of peas (Pisum sativum L.) was studied in comparison with nitrogen fertilizer. The efficiency of the Rhizobium strains varied with their origin and all strains isolated from one local soil in Teresópolis, RJ proved to be equal or superior to two of the strains used in commercial inoculation in Rio Grande do Sul. All three strains isolated from another Teresópolis local produced inefficient nodules as evaluated by the regression of plant N over nodule weight and by the specific nitrogenase activity (umol C2H4/h/g nodules). Plant nitrogen and pod yields with the best Rhizobium strains in all three experiments were equal or superior to the application of 100 kg/ha N.
Keywords: fixation; inoculants